2013
DOI: 10.1111/jir.12102
|View full text |Cite
|
Sign up to set email alerts
|

Family well‐being in a participant‐directed autism waiver program: the role of relational coordination

Abstract: Our findings highlight the importance of establishing a collaborative partnership with waiver families in promoting family well-being. These results suggest that training and/or resources that foster team building and communication can positively impact family functioning among families with young children with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…This was true regardless of whether the child received services through the Autism Waiver program or was on the registry list, and also while controlling for a series of variables, including age. This finding is consistent with other studies that report a relationship between partnerships and increased family satisfaction, more feelings of confidence and respect, and decreased stress (Burke & Hodapp, ; Warfield et al, ; Whitaker, ; Zablotsky et al, ; Zionts et al, ). The family quality of life scale used in the current study measures constructs similar to those cited in previous research, including emotional well‐being and satisfaction with disability‐related support (Burke & Hodapp, ; Brookman‐Frazee, ; Starr & Foy, ; Warfield et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was true regardless of whether the child received services through the Autism Waiver program or was on the registry list, and also while controlling for a series of variables, including age. This finding is consistent with other studies that report a relationship between partnerships and increased family satisfaction, more feelings of confidence and respect, and decreased stress (Burke & Hodapp, ; Warfield et al, ; Whitaker, ; Zablotsky et al, ; Zionts et al, ). The family quality of life scale used in the current study measures constructs similar to those cited in previous research, including emotional well‐being and satisfaction with disability‐related support (Burke & Hodapp, ; Brookman‐Frazee, ; Starr & Foy, ; Warfield et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…For example, mothers of children with autism who engaged in positive parent–professional partnership with their child's service providers reported less stress and higher confidence than mothers engaged in clinician‐directed services (Brookman‐Frazee, ). Higher perceived levels of collaboration with professionals during the diagnosis process in particular (Moh & Magiati, ), and more positive perceptions of the quality of ongoing coordination between parents and the child's service providing agency (Warfield, Chiri, Leutz, & Timberlake, ), are both associated with decreased parental stress. Quality of family–professional partnerships is correlated with and predictive of feelings of parental empowerment among parents of children with disabilities (Dempsey & Dunst, ; Dunst & Dempsey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Those aiming to improve satisfaction with care and well‐being of informal caregivers should therefore look for ways to improve both PCC as well as stimulate productive interactions between professionals and informal caregivers. These findings are consistent with those of Warfield et al () and Weinberg et al () who also found that relational co‐creation of care predicted better outcomes for informal caregivers, such as lower parenting stress, better family functioning, and better caregiver preparation to provide care at home. Looking at the mean scores given by informal caregivers to the various professionals involved in the care delivery to PWID, it seems that informal caregivers interact best with the personal and general support workers; these professionals were also assessed relatively higher in terms of relational co‐creation of care.…”
Section: Discussionsupporting
confidence: 91%
“…Higher mean scores indicated better co‐creation, thus better communication between care providers and informal caregivers as well as respect, desire to share knowledge and goals from the side of care providers. This instrument has proven to be reliable in several studies among informal caregivers in general as well as informal caregivers of PWID (e.g., Warfield, Chiri, & Leutz, ; Weinberg, Lusenhop, & Gittell, ). The Cronbach's alpha of this instrument was 0.98 in this study, indicating excellent reliability.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the previous study [Estes et al, 2014], therapists spent less than 10 min while parents spent 30-40 min directly interacting with the child in each 1-hr session, because they emphasized the collaborative coaching process and parental learning within the sessions. We thought that more modeling from therapists to parents would improve parent's mastery of techniques, but neglected the possible stress-reducing effects of collaborating and guided intervention practice, which have been reported in several earlier studies [Brookman-Frazee, 2004;Gray, Msall, & Msall, 2008;Moh & Magiati, 2012;Warfield, Chiri, Leutz, & Timberlake, 2014;Russa, Matthews, & Owen-DeSchryver, 2015].…”
Section: Effects Of P-esdm On Parenting Stress Of Asd Toddlersmentioning
confidence: 99%